Deciphering Tacrolimus‐Induced Toxicity in Pancreatic β Cells. Issue 11 (1st June 2017) - Triñanes, J.; Rodriguez‐Rodriguez, A. E.; Brito‐Casillas, Y.; Wagner, A.; De Vries, A. P. J.; Cuesto, G.; Acebes, A.; Salido, E.; Torres, A.; Porrini, E.
Abstract : β Cell transcription factors such as forkhead box protein O1 (FoxO1), v‐maf musculoaponeurotic fibrosarcoma oncogene homolog A (MafA), pancreatic and duodenal homeobox 1, and neuronal differentiation 1, are dysfunctional in type 2 diabetes mellitus (T2DM). Posttransplant diabetes mellitus resembles T2DM and reflects interaction between pretransplant insulin resistance and immunosuppressants, mainly calcineurin inhibitors (CNIs). We evaluated the effect of tacrolimus (TAC), cyclosporine A (CsA), and metabolic stressors (glucose plus palmitate) on insulinoma β cells in vitro and in pancreata of obese and lean Zucker rats. Cells were cultured for 5 days with 100 μM palmitate and 22 mM glucose; CsA (250 ng/mL) or TAC (15 ng/mL) were added in the last 48 h. Glucose plus palmitate increased nuclear FoxO1 and decreased nuclear MafA. TAC in addition to glucose plus palmitate magnified these changes in nuclear factors, whereas CsA did not. In addition to glucose plus palmitate, both drugs reduced insulin content, and TAC also affected insulin secretion. TAC withdrawal or conversion to CsA restored these changes. Similar results were observed in pancreata of obese animals on CNIs. TAC and CsA, in addition to glucose plus palmitate, induced comparable inhibition of calcineurin and nuclear factor of activated T cells (NFAT); therefore, TAC potentiates glucolipotoxicity in β cells, possibly by sharing common pathways of β cell dysfunction. TAC‐induced β cell dysfunction is potentially reversible. Inhibition of the calcineurin–NFAT pathway may contribute to the diabetogenic effect of CNIs but does not explain the stronger effect of TAC compared with CsA. Abstract : Tacrolimus, but not cyclosporine, potentiates glucolipotoxicity in β cells by sharing common pathways of β cell dysfunction, while the inhibition of the calcineurin–NFAT pathway does not explain the greater diabetogenic effect of tacrolimus compared to cyclosporine.